A SOCIOLINGUISTIC CASE STUDY: ILLOCUTIONARY SPEECH ACTS ANALYSIS ON BIMA YUDHO SAPUTRO’S CRITICISM OF LAMPUNG GOVERNMENT - Rangkuti, Rahmadsyah; Maulida, Dini Eka; Andira, Missy Ayu; Balqis, Shafiah (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2023)
This research focused on the types of illocutionary acts as the part of speech act use in criticism, specifically on Bima Yudho Saputro’s Criticism of Lampung Government that recently gone viral in Indonesia. The objective of this research is to find out the illocutionary acts used by Bima on his criticism. The methodology applied in this research is qualitative research with case study as the research design, and documentation as the research technique. There are 15 illocutionary speech acts in the criticism found, with 60% of representative utterance, 20% directive utterance, and 20% of expressive utterance. The result show the most frequent illocutionary speech act found in the data is representative. The researchers found the criticism indicates that Bima, the critic, mostly used his words to affirm the truth of a claim he made about something in his criticism. Cutting (2002: 17) provided evidence to support this conclusion when he said that representative speech or utterance are performances in which the speaker's beliefs are expressed through the use of language.